GAMBARAN PERILAKU MASYARAKAT TERHADAP PEMANFAATAN PROGRAM JAMINAN PERSALINAN (JAMPERSAL) DALAM MELAKUKAN PERSALINAN DI PUSKESMAS NAMORAMBE KABUPATEN DELI SERDANG - Dinna Riza Sary; Tukiman .; R. Kintoko Rochadi (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2015)
ABSTRACTJampersal program was started on June 2011 in Deliserdang regency. However,the program has not well-done in all districts including in Namorambe district. It can beseen that some people do not know the Jampersal program from the government.The objective of this program is to know the behavior of the people to the use ofJampersal Program as the place for delivery in Community Health Service in Namorambe,Deliserdang regency. This research used Cross Sectional design. The population was allmothers who delivered in 2012 and resided in working area in Community Health Servicein Namorambe, Deliserdang regency for 812 mothers. The sample was for 87 mothers.The data of age, education, occupation, income, knowledge, attitude and action weretaken through interview using questionnaire. The collected data was analyzeddescriptively and presented in the table frequency distribution.The result of research showed that mostly of the respondents were dominated byage ³ 29 years old (54.7%). Seen from the background of education, it was dominated bymedium education (74.4%). Based on type of occupation, it was dominated by farmers for46.5% and with highest income 55.8%. Mostly of the respondents had low knowledge(57.0%), medium attitude (51,2%) and low action (52.3%). 38.4% checked theirpregnancy using Jampersal for 38.4% and delivered using Jampersal for 38.4% and usingJampersal as postpartum service for 38.4% and 36,0% of the mothers followed FamilyPlanning Program after postpartum.It is suggested for Community Health Service in Namorambe, Deliserdang regencyand village government officers to give information about Jampersal Program routinelyand wholly to the people in Integrated Health Service or in mothers religion groups.Key words: Behavior, Use, Jampersal